Gadolinium(III) Porphyrinoid Phototheranostics. Issue 10 (5th April 2022) - Jin, Guo‐Qing; Lai, Haoqiang; Yang, Zi‐Shu; Ning, Yingying; Duan, Linqi; Zhang, Jing; Chen, Tianfeng; Gao, Song; Zhang, Jun‐Long
Abstract: Molecular phototheranostics as an emerging field of modern precision medicine has recently attracted increasing research attention owing to non‐invasiveness, high precision, and controllable nature of light. In this work, we reported promising gadolinium (Gd 3+ ) porphyrinoids as phototheranostic agents for magnetic resonance imaging (MRI) and photodynamic therapy (PDT). The synthesized Gd‐1‐4‐Glu featured with meso ‐glycosylation and β ‐lactonization to endow good biocompatibility and improved photophysical properties. In particular, β ‐lactonization of glycosylated Gd 3+ porphyrinoids substantially red‐shifted Q band absorption to near‐infrared (NIR) region and boosted generation of reactive oxygen species including 1 O2, and some radical species that engaged in both type II and type I PDT pathways. In addition, the number and regioisomerism of β ‐oxazolone moieties was observed to play an essential role in improving longitude relaxivity ( r 1 ) of Gd‐1‐4‐Glu of up to 4.3±0.2 mM −1 s −1 by affecting environmental water exchange. Taking Gd‐4‐Glu as a promising complex, we further achieved real‐time T1 ‐weighted MRI and PDT on HeLa tumour mice in vivo, revealing the appealing potential of Gd 3+ porphyrinoids in phototheranostics. Abstract : Herein, we report biocompatible Gd 3+ molecular phototheranostic agents (Gd‐1‐4‐Glu ) that are constructed based on porpholactone chemistry for magnetic resonance imaging (MRI) and photodynamic therapy (PDT). We firstly reported that regioisomerism of β ‐oxazolone moieties showed significant effects on environmental water exchange. Furthermore, we achieved real‐time T1 ‐weighted MRI and PDT on HeLa tumour mice in vivo, that reveals the appealing potential of Gd3+ porphyrinoids in phototheranostics.